Fish exposure to nano-TiO2 under different experimental conditions: Methodological aspects for nanoecotoxicology investigations - Clemente, Z.; Castro, V. L.; Feitosa, L. O.; Lima, R.; Jonsson, C. M.; Maia, A. H N; Fraceto, L. F. [UNESP] (Elsevier, 2013)
The ecotoxicology of nano-TiO2 has been extensively studied in recent years; however, few toxicological investigations have considered the photocatalytic properties of the substance, which can increase its toxicity to aquatic biota. The aim of this work was to evaluate the effects on fish exposed to different nano-TiO2 concentrations and illumination conditions. The interaction of these variables was investigated by observing the survival of the organisms, together with biomarkers of biochemical and genetic alterations. Fish (Piaractus mesopotamicus) were exposed for 96h to 0, 1, 10, and 100mg/L of nano-TiO2, under visible light, and visible light with ultraviolet (UV) light (22.47J/cm2/h). The following biomarkers of oxidative stress were monitored in the liver: concentrations of lipid hydroperoxide and carbonylated protein, and specific activities of superoxide dismutase, catalase, and glutathione S-transferase. Other biomarkers of physiological function were also studied: the specific activities of acid phosphatase and Na,K-ATPase were analyzed in the liver and brain, respectively, and the concentration of metallothionein was measured in the gills. In addition, micronucleus and comet assays were performed with blood as genotoxic biomarkers. Nano-TiO2 caused no mortality under any of the conditions tested, but induced sublethal effects that were influenced by illumination condition. Under both illumination conditions tested, exposure to 100mg/L showed an inhibition of acid phosphatase activity. Under visible light, there was an increase in metallothionein level in fish exposed to 1mg/L of nano-TiO2. Under UV light, protein carbonylation was reduced in groups exposed to 1 and 10mg/L, while nucleus alterations in erythrocytes were higher in fish exposed to 10mg/L. As well as improving the understanding of nano-TiO2 toxicity, the findings demonstrated the importance of considering the experimental conditions in nanoecotoxicological tests. This work provides information for the development of protocols to study substances whose toxicity is affected by illumination conditions. © 2013 Elsevier B.V..
Keywords: Biomarkers; Ecotoxicology; Nanotoxicity; Oxidative stress; Titanium dioxide; Ultraviolet light; Acid phosphatase activities; Eco-toxicology; Experimental conditions; Glutathione-S-transferase; Illumination conditions; Physiological functions; Ultra-violet light; Blood; Brain; Carbonylation; Ecology; Fish; Isomers; Light; Oxygen; Phosphatases; Proteins; Toxicity; acid phosphatase; adenosine triphosphatase (potassium sodium); catalase; glutathione transferase; lipid hydroperoxide; metallothionein; nanoparticle; superoxide dismutase; titanium dioxide; biomarker; concentration (composition); ecotoxicology; experimental study; fish; inhibition; mortality; physiological response; pollution exposure; titanium; animal cell; animal experiment; animal tissue; brain level; comet assay; concentration response; controlled study; environmental exposure; enzyme activity; enzyme inhibition; erythrocyte; genotoxicity; light exposure; liver level; micronucleus test; nanobiotechnology; nonhuman; outcome assessment; oxidative stress; pacu (fish); Piaractus mesopotamicus; priority journal; protein carbonylation; ultraviolet radiation